CRISPR/Cas9-mediated generation of hESC lines with homozygote and heterozygote p.R331W mutation in CTBP1 to model HADDTS syndrome - Akdas, Enes Yagiz; Turan, Sören; Guhathakurta, Debarpan; Ekici, Arif Bülent; Salar, Seda; Lie, Dieter Chichung; Winner, Beate; Fejtová, Anna (Stem Cell Research, 2023)
C-terminal Binding Protein 1 (CTBP1) is a ubiquitously expressed transcriptional co-repressor and membrane trafficking regulator. A recurrent de novo c.991C>T mutation in CTBP1 leads to expression of p.R331W CTBP1 and causes hypotonia, ataxia, developmental delay, and tooth enamel defects syndrome (HADDTS), a rare early onset neurodevelopmental disorder. We generated hESCs lines with heterozygote and homozygote c.991C>T in CTBP1 using CRISPR/Cas9 genome editing and validated them for genetic integrity, off-target mutations, and pluripotency. They will be useful for investigation of HADDTS pathophysiology and for screening for potential therapeutics.
CRIS-Team Scopus Importer:2023-01-20